Binatang dalam Sesenggak Sasak: Kajian Etnolinguistik - Nursaly, Baiq Rismarini; Ernawati, Titin (Universitas Hamzanwadi, 2021)
Sesenggaq in the culture of the Sasak tribe are everyday expressions used. In Indonesian language terms sesenggaqis same as proverbs. The proverb itself in the Main Indonesian Dictionary is explained as; groups of words or sentences that have a fixed structure, impose specific intentions and are short, compact expressions or sentences, containing comparisons, parables, advice, principles of life or rules of behavior. This paper reveals about the use of